DIKOTOMI BUDAYA SUNGAI PADA AWAL MASA PERKEMBANGAN BUDAYA ISLAM DI DAS BARITO - Imam Hindarto (Balai Arkeologi Kalimantan Selatan, 2009)
Ecology an area will have an effect on to cultural character of society occupying it. Related to assumption, emerge a problems concerning difference of cultural character of society inhabiting DAS Barito start from upstream go downstream. Distribution analysis or archaeology remain distribution expected will assist in depiction of archaeology data distributions pattern in linear area. Pursuant to result of the analysis hence seeing that to be are cultural character dichotomy from among society upriver and downstream of DAS Barito of difference of ecology.